O TELETRABALHO NA UNIVERSIDADE E PROCESSOS DE COMUNICAÇÃO - Costa, Greicy Mara França Queiroz da (2004)
The present study analyzes the significance and the implications of telework in the professorship of college level in Brazil, objectifying to demonstrate the benefits and applications derived of this process for the practical college teacher, also the ample functional fan derived from telework applied in the work of the university professor. Using a study of case promoted together to the professors of the Federal University of Mato Grosso do Sul (UFMS), the research evaluates the relation of the teaching work with telework and, also, the impacts, benefits and problems that will be able to occur in result of the implantation of telework for the professors of the UFMS. Consequently, a quantitative and descriptive analysis was made, being that the analysis descriptive statistics served of base for generics inferences of qualitative nature. From the results of the field research, that used as main instrument questionnaire with open and closed questions, the study concludes inside that telework is a viable possibility and, on its limitations, beneficial for the superior teaching work.